DINASTI SALAJIKAH (Pembentukan, Kemajuan, Kemunduran dan Kehancurannya) - Dr. Zainuddin Hamkah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
Salajikah government is one of the most important rule in the history of Islam in general, and the history of the East, and Iran in particular. At its inception, realized unity and solid in one command and in the government institutions Salajikah ruling within a period long enough began centuries XI to XII and was officially established in the year 432 H/1040 M, during the time of power Toghur Bek and mancapai golden peak and its glory during the reign of Sultan Alp Arslan and Malikshah, and the decline in the death of Sultan Mas'udi in 547 H / 1152 M